Examining Students' and Educators' Attitudes Towards the use of Code-Switching within Higher Educational Environments in Oman - Al-Qaysi, Noor Jasim Muhi (2016)
Multilanguage speakers have observed a widespread trend of utilizing different utterances. This phenomenon is entitled code-switching or (CS). Switching between two languages in foreign language settings is considered a beneficial communicative strategy for bilingual students and supports the educators in transferring and clarifying the meanings to their students. This study addresses the latest studies regarding the students and educators’ attitudes towards the adoption of CS in the context of higher education. It has been noticed that CS has not yet been explored intensively in the higher educational institutions of the Arab Gulf region; the reason that attracted us to conduct this study and concentrate on Oman (one of the Arab Gulf region countries). Students and educators’ attitudes are the main constructive issues in adopting and implementing CS. The aim of this study is to explore the educators and students/learners’ attitudes towards the adoption of CS in the context of higher education in Oman. Two questionnaire surveys were conducted (one for students and the other for educators). Two interviews were administrated (one for students and the other for educators). Data was collected from Al Buraimi University College (one of the leading Colleges in Oman). 338 students and 21 educators participated within the study. Results ensure that CS can be one of the encouraging and effective educational approaches as to be deployed in the context of higher education at the Gulf region (specifically Oman).